α7 nicotinic acetylcholine receptors in the medial prefrontal cortex control rewarding but not aversive memory expression in a dopamine-sensitive manner - Pastor, Verónica (2023)
Emotional learning involves the association between sensory cues and rewarding or aversive stimuli, and this stored information can be recalled during memory retrieval. In this process, the medial prefrontal cortex (mPFC) plays an essential role. We have previously shown that the antagonism of α7 nicotinic acetylcholine receptors (nAChRs) by methyllycaconitine (MLA) in the mPFC blocked cue-induced cocaine memory retrieval. However, little is known about the involvement of prefrontal α7 nAChRs in the retrieval of aversive memories. Here, by using pharmacology and different behavioral tasks, we found that MLA did not affect aversive memory retrieval, indicating a differential effect of cholinergic prefrontal control of appetitive and aversive memories. Despite being shown that acetylcholine modulates dopamine release in the mPFC, it remains unknown if those modulatory systems act together to control reward-based behavior. We examined that question and found that dopamine type 1 receptor (D1R) activation prevented MLA-induced blockade of cocaine CPP retrieval. Our results suggest that α7 nAChRs and D1R signaling interact in the mPFC to modulate cocaine-associated memory retrieval.